Influence Concentration and Immersion Time, Substance Regulator Growth of IBA (Indole-3-Butyric Acid) Against Early Seedling Growth Cuttings, Plant Jasmine White (Jasminum sambac) - Ridwan Fajri; Nova Triani; Pangesti Nugrahani (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
White jasmine (Jasminum sambac (L.) Aiton) is an ornamental plant of high economic value that requires access to quality, uniform seeds. Propagation through stem cuttings often faces challenges in root formation and initial growth. This study aims to analyze the effects of Indole-3-Butyric Acid (IBA) concentration and soaking time on the initial growth of white jasmine cuttings. The study employed a factorial completely randomized design with two factors: IBA concentration (0, 50, 100, and 150 parts per million) and soaking time (30, 60, and 90 minutes). The parameters observed included shoot emergence time, shoot length, number of leaves, number of primary roots, and root fresh weight. Data were analyzed using analysis of variance at a 5% significance level. The results showed a significant interaction between concentration and soaking time for all parameters. The combination of 100 ppm IBA with a 60-minute soaking time resulted in the fastest shoot emergence (11.27 days), the longest shoot length at eight weeks after planting (11.27 cm), the highest number of leaves (12.60), the greatest number of primary roots (12.52), and the largest fresh root weight (1.06 g). Treatments without growth regulators showed the lowest values for most parameters. Thus, a concentration of 100 ppm with a 60-minute soaking time was the most effective combination for enhancing the initial growth of white jasmine cuttings. Applying this treatment has the potential to improve seedling quality and uniformity, supporting the development of white jasmine cultivation.